PROPUESTA DE UN PLAN DE MANTENIMIENTO PREVENTIVO PARA LA EMPRESA LACTEOS SERRANITO - Tipan Sango, Welington Alexander (2023)
With the purpose of improving the efficiency and prolonging the useful life of the machines in the production area of Lácteos Serranito, a proposal for a preventive maintenance plan is presented in this work through the use of Mp software, a CMMS (Management System Computer Aided Maintenance). The company is located in the province of Pichincha, in the Mejía canton, to start the preventive maintenance plan, a complete inventory of the machines in use will be carried out, including their operational status and a unique coding for each of them, which that will facilitate its identification.